Family Instability: A Study of Livelihoods during the Covid-19 Pandemic in Tanah Datar Regency, Indonesia - Elimartati Elimartati; Nailur Rahmi; Widi Nopiardo; Firdaus Firdaus; Vasco Fronzoni (Institut Agama Islam Negeri Batusangkar, 2023)
The Covid-19 pandemic resulted in a decrease in family income. Thus, it gave birth to various forms of difficulties in meeting family needs. Through research, the process of how families survived in earning a living during the Covid-19 pandemic was described. The process included the types of difficulties, impact, and solutions to the difficulties encountered. A qualitative approach was used in conducting this study in which the primary and secondary data were obtained using observation techniques, interviews, focus group discussion, and documentation. The research findings showed that there were three difficulties faced by families from a decrease in their income during the Covid-19 pandemic: difficulties in developing businesses, low family purchasing power, and increasing family needs. These three things then led to family instability with the emergence of conflicts such as domestic violence and divorce which continued to increase during the Covid-19 pandemic. Due to the difficulties, the family made creative business adjustments and got help. Families made business adjustments by looking for alternative sources of income, while external assistance was obtained from community and government institutions. This paper concludes that the creativity developed to meet family needs during a pandemic is urgently needed so that families can continue to survive in difficult conditions.